PELUANG PENGEMBANGAN KELAPA SAWIT DI INDONESIA: PERSPEKTIF JANGKA PANJANG 2025 - WAYAN R. SUSILA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
After experiencing fast growth rates in 1990th, palm oil industry in Indonesiais facing some constraints that make investors have been reluctant to invest in theindustry. The aim of this paper is to analyze prospects and business opportunities ofthe industry, by using a long run time horizon of 2005-2025. The results of analysisindicate that the world CPO consumption is estimated to be around 41.15 – 44.45million tones in 2025. With the world CPO production in 2004 was around 25.67million tones, and then the opportunities to increase production by 2025 wasestimated between 15.78 – 18.78 million tones. Indonesia was predicted to gain thehigher share in capturing this market opportunities (40%) or around 6.31 – 7.51million tones, equivalent to 1.80 – 2.15 million ha of area expansion. Total investmentrequired for area expansion and CPO plants development by 2020 is estimated at Rp57.12 – Rp 67.97 trillion. In capturing these opportunities, investors have to face 22investment constraints, mainly limited funding sources, the negative impacts ofregional autonomy, land conflict, and environmental issue.